A comparison of tonnage-dependent shot blast and electro-discharge texturing methods. (27th September 2021) - Çolak, Bilal
Abstract: This study investigated the surface roughness characteristics of rolls textured using the Shot-Blast Texturing and Electro-Discharge Texturing methods. The rolling tests were carried out in an actual cold rolling mill tandem line, and the surface roughness transferred from the roughened rolls to the material with these two methods was examined. The study measured and compared the surface roughness of roughened rolls and the materials rolled by them. The study observed that the transfer ratio of electro-discharge texturing rolls was higher, but the transfer ratio of SBT rolls increased towards the end of the rolling campaign. The study also examined the extent to which the surface roughness of the rolls changed after rolling. Therefore, the level of reduction and how much was preserved were determined by comparing the surface roughness of the rolls before and after the rolling campaign. Shot-blast texturing rolls were found to have lost 53% of their roughness while electro-discharge texturing rolls lost only 33%.